Parenthetical constructions in the Russian epistolary text of 1700 –1710s: the problem of syntactic qualification - Zuyeva, Volha U. (Journal of the Belarusian State University. Philology, 2019)
The problem of determining of the syntactic status of constructions with an evaluation modal meaning in the Russian epistolary texts of the first decades of the 18th century is considered. This problem is connected with studying of the evolution of the parenthetical category in the history of the Russian language and studying of the formal expression of this category. Functional and semantic groups of constructions are described. It is shown that in this chronological period the syntactic organization of the selected type of discourse is characterized by using both parenthetical constructions and non-related phrases with an evaluation modal meaning. Such phrases are significantly more quantitative and frequency prevailing. It has been established that many units allow different syntactic interpretations due to formal connections with other components of the statement, grammatical homonymy and inability to reconstruct the communicative intention of the author of the text in principle. The need to study formal and grammatical characteristics of modal and evaluative constructions in the Russian language of the pre-national period in order to clarify their syntactic status is concluded.